Experimental evaluation of the usability of palm tree pruning waste (PTPW) as an alternative to geotextile - Kaplan, Ebubekir; Kayadelen, Cafer; Öztürk, Mitat; Önal, Yakup; Altay, Gökhan (Revista de la Construcción. Journal of Construction, 2022)
This paper focuses on serving twofold benefits for the environment by providing not only recycling of a waste material but also improving rutting performance of sand subgrade under cyclic traffic loads. In this context, a series of laboratory experiments have been conducted to benchmark the performance of commercially manufactured geotextile and palm tree pruning waste (PTPW) as soil improvement agents. Experimental results of the study were evaluated based on permanent (plastic), total, and elastic deformation, rut depth reduction (RDR), traffic benefit ratio (TBR), percentage of elastic deformation, and resilient modulus (MR). In the view of experimental results, geotextile and PTPW-reinforced sand subgrades demonstrated well performance in the sense of permanent and elastic deformations when compared to unreinforced case. It is also realized that the most satisfactory performance was obtained when geotextile or PTPW are located at a burial depth of both 50 mm and 100 mm. In that case, TBR values of geotextile and PTPW-reinforced subgrades were almost the same at 20 mm permanent deformation (i.e., 6.71 and 6.76, respectively). Furthermore, when the results were evaluated based on RDR, it is observed that geotextile and PTPW reinforcements reduced the rut depth at the rate of 49.31 % and 37.15 % at the end of 5000 load cycle, respectively.